Measurement of T1 Mapping in Patients With Cardiac Devices: Off-Resonance Error Extends Beyond Visual Artifact but Can Be Quantified and Corrected - Bhuva, Anish N.; Treibel, Thomas A.; Seraphim, Andreas; Scully, Paul; Knott, Kristopher D.; Augusto, João B.; Torlasco, Camilla; Menacho, Katia; Lau, Clement; Patel, Kush; Moon, James C.; Kellman, Peter; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Measurement of myocardial T1 is increasingly incorporated into standard cardiovascular magnetic resonance (CMR) protocols, however accuracy may be reduced in patients with metallic cardiovascular implants. Measurement is feasible in segments free from visual artifact, but there may still be off-resonance induced error. Aim: To quantify off-resonance induced T1 error in patients with metallic cardiovascular implants, and validate a method for error correction for a conventional MOLLI pulse sequence. Methods: 24 patients with cardiac implantable electronic devices (CIEDs: 46% permanent pacemakers, PPMs; 33% implantable loop recorders, ILRs; and 21% implantable cardioverter-defibrillators, ICDs); and 31 patients with aortic valve replacement (AVR) (45% metallic) were studied. Paired mid-myocardial short-axis MOLLI and single breath-hold off-resonance field maps were acquired at 1.5T. T1 values were measured by AHA segment, and segments with visual artifact were excluded. T1 correction was applied using a published relationship between off-resonance and T1. The accuracy of the correction was assessed in 10 healthy volunteers by measuring T1 before and after external placement of an ICD generator next to the chest to generate off-resonance. Results: T1 values in healthy volunteers with an ICD were underestimated compared to without (967±52 vs 997±26ms respectively, p=0.0001), but were similar after correction (p=0.57, residual difference 2±27ms). Artifact was visible in 4±12, 42±31 and 53±27% of AHA segments in patients with ILRs, PPMs and ICDs respectively. In segments without artifact, T1 was underestimated by 63ms (interquartile range: 7-143) per patient. The greatest error for patients with ILRs, PPMs and ICDs were 79, 146 and 191ms respectively. The presence of an AVR did not generate T1 error. Conclusion: Even when there is no visual artifact, there is error in T1 in patients with CIEDs, but not AVRs. Off-resonance field map acquisition can detect error in measured T1, and a correction can be applied to quantify T1 MOLLI accurately.